2018
DOI: 10.1007/s10695-018-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress mediated the inhibition of cerebral creatine kinase activity in silver catfish fed with aflatoxin B1-contaminated diet

Abstract: Aflatoxin B (AFB) is an environmental toxicant and neurotoxic compound that induces the production of free radicals, causing oxidative stress. Creatine kinase (CK) is a central controller of energy metabolism in tissues with a large and fluctuating energy demand, and it is highly susceptible to inactivation by free radicals and oxidative damage. Thus, the aim of this study was to evaluate whether a diet for freshwater silver catfish (Rhamdia quelen) containing AFB inhibits cerebral CK activity, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Studies have shown that AFB1 directly binds to unknown receptors on neuronal cells leading to a dose as well as time-dependent reduction in neuronal cell numbers [1,7]. More studies are needed to identity these unknown receptors.…”
Section: Nervous System Aflatoxin B1 Signaling Pathwaysmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that AFB1 directly binds to unknown receptors on neuronal cells leading to a dose as well as time-dependent reduction in neuronal cell numbers [1,7]. More studies are needed to identity these unknown receptors.…”
Section: Nervous System Aflatoxin B1 Signaling Pathwaysmentioning
confidence: 99%
“…Souza et al demonstrated that, AFB1 was capable of modifying the energetic balance associated with ATP metabolism via the inhibition of a crucial enzyme of cellular homeostasis in cells with high as well as moderate energy needs like brain cells [1]. They indicated further that, the inhibition reduces ATP production as well as the interaction sites of ATP initiation and utilization with a resultant inhibition of cerebral sodium-potassium pump (Na + , K + -ATPase) activities [1]. Na + , K + -ATPase is a fundamental enzyme conscientious for the electrochemical gradient across cell membranes, preservation of membrane potential, cell capacity, cellular, as well as excitatory neurotransmitters [1,29].…”
Section: Nervous System Aflatoxin B1 Signaling Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations